Pengaruh Altman Z-Score Terhadap Realized Return Perusahaan Terbuka di Indonesia - Andre Reinaldi; Devia Alvionita; Vebby Tjakranegara; Yane Chandera; Rathria Arrina Rachman (Universitas Prasetiya Mulya, 2020)
This study aims to examine whether there is a relationship between Altman Z-Score (financial distress predictor) and realized return on company’s stock, and how much the influence of Altman Z-Score on the realized stock returns. One way to find out the company's financial condition is using the Altman Z